Case Report: Cardiac myxomas and Carney complex: a case of recurrent embolic strokes and intracranial tumor growth - Kuhn, Aliny W.; Lerario, Antonio M.; Morais, Alice N. R.; Iglesio, Ricardo F.; Ramires, Félix J. A.; Maluf, Ligia C. A.; Hoff, Ana O.; Latronico, Ana C.; Mendonça, Berenice B.; Almeida, Madson Q.; Fragoso, Maria C. B. V. (Frontiers in Oncology, 2025)
Cardiac myxomas, though rare, are the most common benign cardiac tumors and may be associated with Carney Complex (CNC). Patients with CNC are at increased risk of developing recurrent myxomas, which can lead to severe complications. We report a case of a 46-year-old woman with CNC and recurrent cardiac myxomas who developed multiple embolic strokes and cerebral aneurysms. Following two hemorrhagic strokes, neuroimaging and biopsy revealed a well-differentiated myxoid neoplasm in the brain parenchyma. Genetic analysis revealed a germline pathogenic PRKAR1A variant, along with loss of heterozygosity (LOH) at chromosome 17q24.2 in the cardiac myxoma, but not in the brain lesion. This case challenges the conventional understanding of cardiac myxomas as strictly benign, suggesting they may exceptionally exhibit distant proliferative behavior, likely through mechanical dissemination and subsequent growth in the brain. Although embolic events are common in cardiac myxomas, the capacity of tumor cells to implant and proliferate in extracardiac sites remains poorly understood. Our findings underscore the importance of maintaining a high index of suspicion for neurological complications in patients with cardiac myxomas, particularly in the setting of CNC. Further investigation is essential to elucidate the mechanisms driving this behavior and to optimize management strategies in similar cases.